Current understanding of immune-like responses in worms - Abdul Qadeer; Guofeng Cheng (Comparative Immunology Reports)
The mammalian innate and adaptive immune systems are critically important for defending against pathogen invasion. However, the immune systems of invertebrates are often overlooked. Investigating the immune responses in invertebrates is essential, as they may contribute to unique mechanisms for biological diversity. In this review, we summarized the current understanding of the immune systems of invertebrates, including Caenorhabditis elegans, Anisakis, and planarians, and then highlighted their potentially important functions and pathways associated with immune-like responses. Next, we reviewed the diversity of pattern recognition receptors (PRRs), immune effectors, and signaling pathways in invertebrates to gain insights into their roles in pathogen resistance and long-lasting inducible protection. Finally, we discussed the important implications for developing novel prevention and treatment strategies based on the current understanding of the immune systems in invertebrates.